(Trifluoromethylselenyl)methylchalcogenyl as Emerging Fluorinated Groups: Synthesis under Photoredox Catalysis and Determination of the Lipophilicity. Issue 19 (3rd March 2021) - Grollier, Kevin; De Zordo‐Banliat, Arnaud; Bourdreux, Flavien; Pegot, Bruce; Dagousset, Guillaume; Magnier, Emmanuel; Billard, Thierry
Abstract: The synthesis of molecules bearing (trifluoromethylselenyl)methylchalcogenyl groups is described via an efficient two‐step strategy based on a metal‐free photoredox catalyzed decarboxylative trifluoromethylselenolation with good yields up to 88 %, which raised to 98 % in flow chemistry conditions. The flow methods allowed also to scale up the reaction. The mechanism of this key reaction was studied. The physicochemical characterization of these emerging groups was performed by determining their Hansch–Leo lipophilicity parameters with high values up to 2.24. This reaction was also extended to perfluoroalkylselenolation with yields up to 95 %. Finally, this method was successfully applied to the functionalization of relevant bioactive molecules such as tocopherol or estrone derivatives. Abstract : New, highly lipophilic, fluorinated groups : Through an easy two‐step procedure, with photoredox‐catalyzed decarboxylation key step, molecules with (trifluoromethylselenyl)methylchalcogenyl groups can be easily obtained. These new innovative substituents are among the highest lipophilic fluorinated moieties.